ANALISIS KESULITAN SISWA DALAM KEMAMPUAN BERPIKIR KRITIS UNTUK MENYELESAIKAN SOAL SUKU BANYAK - Susanti, Nawal Ika; Asnawi, Muhammad Hasan (Universitas KH. Mukhtar Syafaat Banyuwangi, 2025)
The purpose of this research is to analyze the level of difficulty students face in critical thinking skills to solve polynomial problems.This research uses a quantitative approach by employing data difficulty level analysis and critical thinking level analysis. The research sample consisted of 30 students from the XI IPA 3 class at SMA Darussalam. The results of this study show the level of students' critical thinking skills in solving polynomial problems consisting of 5 questions. In terms of students' critical thinking abilities, they fall into the critical thinking category on question no. 1 with indicators of identifying, problem-solving, evaluating, and analyzing polynomial problems. Looking at the level of mistakes made by the students, the highest was on question no. 2 with a difficulty percentage of 53.3%, which corresponds to 16 students. Meanwhile, the lowest error rate was on question no. 3, which was 20%, or 6 students.